PENYIDIKAN TINDAK PIDANA PENIPUAN DENGAN MODUS OPERANDI HIPNOTIS OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Purwitosari, Dyah; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Hypnotize is derived from the Greek word, which means Hypnos "sleep". From several sources, obtained little meaning and difference between hypnosis with hypnosis. Hypnotist as a technique to master one's awareness so that people will unknowingly be obedient if given a suggestion or command by actors hypnotic. Encountered in terms of medicine and psychology. In medical terms, hypnosis interpreted as "like sleeping due to suggestion, which is in the spearhead, the man was under the influence of people who give suggestions to him, thus making completely unaware." Quite often the science of hypnosis can be misunderstood and used in committing a crime such as fraud.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide complete and clear picture of the problems that this diteliti.Penelitian do in Pekanbaru City Police. While the sample population is a whole party with regard to the issues examined in the study ini.Sumber data used, primary data and secondary and tertiary of data, data collection techniques in this study with questionnaires, interviews and review of the literature.From this research, there are three main things that can be inferred. The first investigation of criminal fraud with the modus operandi of hypnosis by Police resort city of Pekanbaru by investigators, namely: receive any reports of someone who is experiencing, seeing, or who are victims of a criminal incident happens, perform the first act upon on the spot, make arrests , detentions, searches, seizure, inspection and seizure of letters, fingerprinting and photographing a person suspected of committing a crime, calling the people to be heard and examined as a suspect or a witness, bring in an expert is needed in relation to the case investigation, Conducting investigations termination; Second, obstacles to criminal investigations of fraud with the modus operandi of hypnosis by City Police Pekanbaru happens, among other things, proof that conveyed by the rapporteur, making it difficult or become obstacles in the investigation process. Difficult to trace the perpetrators of fraud with the mode of hypnosis, improve cooperative relationships with related parties, the Third, efforts are being made to overcome the obstacles in the investigation of fraud with the modus operandi of hypnosis by City Police Pekanbaru obstacle would be the lack of evidence of the complainant can tackle by socializing and giving advice to the public, especially the reporting.Keywords: Investigation, Crime, Fraud, Hypnosis